Moving beyond awareness to action and food system transformation: prioritizing labor in food systems governance work - Wilson, Amanda; Tasala, Kirsti (Frontiers in Sustainable Food Systems, 2024)
The COVID-19 pandemic laid bare many of societies' existing social and economic inequalities, one of which is illustrated in the challenges facing food and farm workers across the food chain. Despite this upsurge in public recognition, the circumstances facing food and farm workers remain unchanged, and this lack of action is reflected within the work of food systems-focused civil society organizations (CSO) in Canada. Several authors have noted the lack of recognition of labor issues within food systems work. This paper further explores the nature of this disengagement, particularly in food systems governance work, and identifies barriers to more meaningful engagement and possible avenues to overcome these challenges. Findings draw from a set of 57 interviews conducted from 2020-2023 with a range of food system CSO representatives across Canada, examining their understanding of, and engagement in, food systems governance work and their involvement in labor issues (or lack thereof). The paper concludes that though there exists widespread awareness of the challenges facing food and farm workers, and a desire to engage in a more sustained fashion, many food system CSOs have not yet found the tools or pathways to do so on an organizational level. Several discursive openings are identified that offer an opportunity to leverage the heightened awareness of food and farm workers during the pandemic into concrete collective action.